The effects of vitamin D supplementation on endogen amylin hormone, hormonal and biochemical parameters, and insulin resistance in type-2 diabetic patients with vitamin D deficiency in the Kurdistan Region of Iraq. / Efectos de la suplementacion de Vitamina D sobre la hormona endógena amilina, parámetros hormonales y bioquímicos, e insulina resistencia en pacientes diabéticos tipo 2 con deficiencia de Vitamina D en la región Kurdistan de Irak. - M. Saeed, Mudhafar Mohamed; Al-Naqshabandi, Abdulqader Azeez; Sami Aldawoodi, Hawri Fatih (Investigación Clínica, 2020)
Abstract. The present study was conducted to evaluate the correlations between vitamin D, amylin, c-peptide, insulin, and HbA1c and determine the effects of vitamin D supplementation on the level of these biomarkers in type-2 diabetic patients with vitamin D deficiency. A total of 87 Kurdish type-2 diabetic patients participated in this clinical trial in which biomarkers, including vitamin D (25 hydroxy cholecalciferol), serum amylin, c-peptide, insulin, fasting blood glucose, HbA1c, HDLc, LDLc, total cholesterol, triglycerides, weight, height, waist circumference, and inflammation markers (i.e. IL6, TNF-α, and hsCRP) were measured. Serum levels of vitamin D were positively correlated with serum Amylin, c-peptide, insulin, and HDL, while it had negative correlations with HbA1c, fasting blood sugar, IL6, TNF-α, hs-CRP, LDL, and triglycerides. After 14 weeks of supplementation with vitamin D (5000 IU/day) there were significant increases in plasma amylin, c-peptide, and insulin concentrations; but the levels of HbA1c, fasting blood glucose, TNF-α, hs-CRP, and IL6 were significantly decreased. It can be concluded that vitamin D supplementation can potentially regulate blood glucose by activating the secretory function of pancreatic B-cells and reducing insulin resistance through a significant reduction in a circulatory level of inflammatory markers.Resumen. El presente estudio se realizó para evaluar las correlaciones entre la vitamina D, la amilina, el péptido C, la insulina y la HbA1c y determinar los efectos de la suplementación con vitamina D en el nivel de estos biomarcadores en pacientes diabéticos tipo 2 con deficiencia de vitamina D. Un total de 87 pacientes kurdos, diabéticos tipo 2, participaron en este ensayo clínico en el que se midieron los biomarcadores, incluídos la vitamina D (25 hidroxicolecalciferol), amilina sérica, péptido C, insulina, glucosa sérica en ayunas, HbA1c, HDLc, LDLc, colesterol total, triglicéridos, peso, altura, la circunferencia de la cintura y los marcadores de inflamación (es decir, IL6, TNF-α y hs-CRP). El nivel sérico de vitamina D se correlacionó positivamente con la amilina sérica, el péptido C, la insulina y el HDLc, mientras que tuvo correlaciones negativas con HbA1c, glucosa en sangre en ayunas, IL6, TNF-α, hs-CRP, LDLc y triglicéridos. Después de 14 semanas de suplementación con vitamina D (5000 UI / día) hubo aumentos significativos en las concentraciones plasmáticas de amilina, péptido C e insulina; pero los niveles de HbA1c, glucosa en sangre en ayunas, TNF-α, hs-CRP e IL6 disminuyeron significativamente. Se puede concluir que la suplementación con vitamina D puede potencialmente regular la glucosa en la sangre activando la función secretora de las células B pancreáticas y reduciendo la resistencia a la insulina a través de una reducción significativa en un nivel circulatorio de marcadores inflamatorios.